Women and research in British universities – an institutional case study. (17th January 2012) - Fisher, Virginia
This paper explores the experiences of, and the challenges faced, by women academics attempting to build successful research careers. It draws upon both the already significant literature on the topic and the results of a six month research project. This project included the recording and analysis of 41 in depth, semi structured interviews with women researchers and research managers. The interviews were conducted by the author as part of an internally funded research project located in one large, British, post 1992, University. The research was commissioned by the Graduate School and the Equality and Diversity Unit as a reaction to the serious under–representation of women academics in both the Research Assessment Exercise 2008 and as members of the university professoriate. This case study demonstrates that many women researchers must overcome a series of institutional and socially constructed hurdles before they can fully realise their academic research potential.